Humanity in James Dashner's The Maze Runner - Kokešová, Barbora (Univerzita Pardubice, 2023)
The bachelor thesis focuses on humanity. It looks in detail at the main attributes of the concept of "humanity" and highlights the effects that extreme living conditions and separation from society have on the nature of humanity. It also reflects on the notion of "justifying the means to an end" and exemplifies morally wrong acts performed in the name of humanity. It analyses the presence of humane and inhumane aspects in James Dashner's The Maze Runner series, supported by various excerpts from the novels.
Lidskost v díle The Maze Runner Jamese Dashnera
Keywords: lidskost; komunita; morálka; morální hodnoty; manipulace; izolace; humanity; community; morality; moral values; manipulation; isolation